Unpacking non-institutional engagement: Collective, communicative and individualised activism. (February 2021) - Slavina, Anna
This paper disaggregates non-institutional political engagement into three distinct repertoires of activism: collective, communicative and individualised forms. I evaluate the claim that non-institutional activism is more inclusive than traditional forms of political engagement by measuring the relative effects of typical predictors of participation, including resources, values and contextual measures, on different repertoires of non-institutional engagement. The findings suggest that individualised engagement is more accessible to women but stratified by resources and national wealth. Collective engagement is more accessible to people from disadvantaged socioeconomic backgrounds but is stratified by gender, with women less likely to engage.